Prosedur Pelaksanaan Operasi Pasar Lumbung Pangan Jawa Timur: Mendorong Kesejahteraan Masyarakat Melalui Akses Terhadap Pangan Yang Terjangkau - Yemima Marchely Rawung; Muhammad Agus Muljanto (Lembaga Pengembangan Kinerja Dosen, 2023)
In this study, researchers approached the study through theory and physics. Surabaya has established itself as a city of services and commerce. In addition, Surabaya is a business city where various events take place. As a shop, Surabaya is a one-stop shop. All activities take place here and all supporting facilities are available. Trading is the main activity in Surabaya. Geographically, Surabaya actually emerged as a commercial city. Since the colonial era, the kingdom of the Majapahit era, trade has become the main activity. Currently trading activities in Surabaya are not limited to regional and national needs. Surabaya has become a city of international trade. As a commercial city, Surabaya has several important pillars. These places become spaces for commercial activities. The modern market is the most important pillar of Surabaya's status as a commercial city. Attractive layout, comfortable atmosphere, and competitive prices are the hallmarks of a modern market that fits with the dense activity of city dwellers. Modern markets are scattered throughout the center and suburbs of Surabaya. The presence of many modern markets provides more choices for the community. This number will continue to grow as investment in Surabaya increases. Kampung Surabaya is a living space for Surabaya residents. Apart from houses, villages in Surabaya are also production centers. The village is now emerging as a small economic center. Each village has its own special food, pastries, jewelry, clothing and more. Due to the influence of the city government, these villages are now designated as leading villages and have the potential to strengthen the economy of the less fortunate.